2020
DOI: 10.1111/cts.12877
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Clinical Pharmacology of T‐Cell Engaging Bispecifics: Current Perspectives and Opportunities

Abstract: T-cell directing/engaging bispecifics (TDBs) enable a powerful mode of action by activating T-cells through the creation of artificial immune synapses. Their pharmacological response involves the dynamic interrelationships between T-cells, tumor cells, and TDBs. This results in complex and challenging issues in understanding pharmacokinetics (PK), tissue distribution, target engagement, and exposure-response relationship. Dosing strategy plays a crucial role in determining the therapeutic window of TDBs becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…In comparing simulations of the trispecific with a comparable bispecific molecule without CD28 targeting, we find that CD28 does give significant benefit at lower doses. This finding may be more relevant to the clinical active dose than the predictions for higher doses, as many T-cell engaging drugs show high potency at low doses 27 . Furthermore, CD28 engagement keeps a higher proportion of T cells activated for longer period without necessarily leading to exhaustion 34 , 35 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In comparing simulations of the trispecific with a comparable bispecific molecule without CD28 targeting, we find that CD28 does give significant benefit at lower doses. This finding may be more relevant to the clinical active dose than the predictions for higher doses, as many T-cell engaging drugs show high potency at low doses 27 . Furthermore, CD28 engagement keeps a higher proportion of T cells activated for longer period without necessarily leading to exhaustion 34 , 35 .…”
Section: Discussionmentioning
confidence: 95%
“…When aligning model predictions with preclinical and clinical responses, trimer concentration has been found not to adequately describe dose–response and additional constructs such as active T-cell numbers, or T-cell potency, have been linked to cytotoxicity to better explain the data 26 . Furthermore, several studies and reviews discuss the complexity of dose–response found for bispecific antibodies in the clinic and the differential success of this drug in patients with different levels of disease 27 . Our model attempts to extend the understanding of dose–response to trispecific T-cell engagers, and to generate a consolidated perspective of what controls dose–response in these modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the BsAb formats and MOAs, utilizing control BsAbs with null binding arms can be critical in assessing individual TE versus dual TE, and the associated functions (Sup Ref 8). More sophisticated and extensive in vivo biodistribution and functional (PK/TE/PD) studies using advanced techniques such as imaging 8 have been shown to enhance the understanding of the MOA(s) of a BsAb and to enable smarter design of a construct including the selection of binding affinities and epitopes of each arm based on experimental data 9 (Sup Ref 9) and quantitative modeling & simulation approaches (Sup Ref 10, 11) 10 . The learnings are valuable from preclinical animal models (particularly the determination of how both arms of the BsAb construct impact tissue distribution), in vivo TE and RO, and combined PD outcomes compared with a mAb combination approach for translational medicine considerations and early clinical development.…”
Section: Biology Biophysics and Pharmacology Driven Research And Deve...mentioning
confidence: 99%
“…Three BsAbs, blinatumomab (BLI; anti-CD3/CD19) and mosunetuzumab and RNGN1979 (both anti-CD3/CD20), are already approved by the US Food and Drug Administration (FDA) for treating human hematopoietic malignancies, 3 and more than 60 additional BsAbs are currently in preclinical and clinical development. 4 Another BsAb, catumaxomab, was approved for treating malignant ascites but was withdrawn from the market in 2017. BsAbs work by directing T cells to kill cancer cells via a cytolytic immune synapse formed between the two cell types.…”
Section: Introductionmentioning
confidence: 99%